Feeding Difficulties in Children with Cerebral Palsy: Prevalence and Risk Factor - Nur, F T; Handryastuti, S; Poesponegoro, H D (KnE Life Sciences, 2019)
Cerebral palsy (CP) is a motor and postural disorder due to an injury on the developing brain. Children with severe motor impairment are likely to have more difficulties in feeding. This results in inadequate calorie intake which finally leads to malnutrition. A cross-sectional study was done between January-September 2015 in a pediatric neurology outpatient-clinic, at a tertiary hospital in Surakarta, Indonesia. Children with CP underwent the Gross Motor Function Classification System (GMFCS) scale, nutritional and feeding difficulties assessment. The GMFCS was evaluated by Gross Motor Function Measure-88. Nutritional status was determined and classified based on Waterlow. Spastic quadriplegic patients were also compared to Krick’s CP growth curve. Calorie intake was evaluated by dietary analysis and defined as adequate if it reached 13,9 kcal/cm body height (BH)±10%. Most of the CP patients were the spastic type (77/80,96%), dominated by quadriplegic and diplegic types. Malnutrition was found in 78% of subjects. Feeding difficulties were found in 78% of subjects, about a third of them was categorized as having high GMFCS scale. The prevalence of undernourished and severe malnutrition in children with CP is 68% and 10%, respectively. The higher GMFCS scale and CP with spastic type are risk factors of feeding difficulties in children with CP.